Effect of Age at Castration on Beef Calf Performance - Amie Imler; Todd Thrift; Matt Hersom; Joel Yelich (EDIS)
A study in Florida was conducted to examine the issue of age at castration to determine if castration timing resulted in significant differences in growth rate and weaning weight in nursing calves. In addition, the study included a comparison between Angus and Brangus calves in the treatment groups to determine if there was a breed by castration effect. No differences in calf growth rates were observed in early compared to late castration. This 4-page fact sheet was written by Amie Imler, Todd Thrift, Matt Hersom, and Joel Yelich, and published by the UF Department of Animal Sciences, March 2013.